2020
DOI: 10.3390/healthcare8020091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pediatric Surgical Site Infections Associated with Colorectal Surgeries at an Academic Children’s Hospital

Abstract: Appropriate use of antibiotic prophylaxis (AP) is a key measure for the prevention of surgical site infections (SSI) in colorectal surgeries; however, despite the presence of national and international guidelines, compliance with AP recommendations remains low. The purpose of this study is to evaluate compliance with recommendations for the use of AP in children undergoing colorectal surgeries and to evaluate the effectiveness of antibiotics in the prevention of SSI. We collected demographic and clinical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
10
1
1
Order By: Relevance
“…In our study, the number of dirty wounds was higher due to the fact that our center was a referral hospital. In a study in USA in 2020 on colorectal procedures, the percentages of clean/contaminated, contaminated, and dirty wounds were 68%, 17%, and 15%, respectively, showing a higher value in the case of contaminated wounds compared to our study because of the nature of their procedure (20).…”
Section: Cleft Palate -Clean Wound Cefotaxime Cefazolincontrasting
confidence: 66%
“…In our study, the number of dirty wounds was higher due to the fact that our center was a referral hospital. In a study in USA in 2020 on colorectal procedures, the percentages of clean/contaminated, contaminated, and dirty wounds were 68%, 17%, and 15%, respectively, showing a higher value in the case of contaminated wounds compared to our study because of the nature of their procedure (20).…”
Section: Cleft Palate -Clean Wound Cefotaxime Cefazolincontrasting
confidence: 66%
“…The most frequently detected pathogens detected in pediatric and neonatal SSIs are shown in Table 3 [22,27,29,32,33,[38][39][40][41]43]. 1 Some patients had cultures positive for more than one bacteria species.…”
Section: Etiology Of Ssis In Children and Neonatesmentioning
confidence: 99%
“…A single centre study carried out in Arkansas (USA) reported a 6.25% rate of SSI in children who had undergone colorectal surgery. Emergent surgery was burdened with a higher risk of SSI, as well as longer-lasting surgeries and hyperglycaemia [ 27 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Pough and colleagues explore variations in antibiotic administration and compliance with prophylaxis standards and identify opportunities for further reductions in surgical site infection in pediatric colorectal surgery populations [ 3 ]. They identify an approach to address these consistent with ERAS ® protocols.…”
mentioning
confidence: 99%